Motivos Que Conllevan A La Elección Académica De Licenciatura En Educación Física Y Deportes En La Universidad Del Quindío (2014)
Nowadays, the higher education system has been having a series of problems, and among them the most common has been the students’ hesitation when choosing their career; which makes them take wrong decisions affecting them in an economical, personal and occupational level. Therefore, this research aimed to clarify the reasons that led students to choose the Degree in Physical Education and Sports from the University of Quindío as their career. To accomplish this goal was necessary to employ a qualitative case-study research; which allows a more global and comprehensive approach to reality. Besides, this research was made with a comprehensive approach that allows studying society through the interpretation of the individual behavior to understand and explain its causes and effects. On the other hand, the semi-structured and in-depth interview were used to collect the data; which allowed knowing the specific reasons that made students chose this career. As a result, the main reasons that made students choose the Degree in Physical Education and Sports were: the academic training, need for income, better job opportunities, affinity sports, and hasty decisions